Design, construction and evaluation of a drone-tethered river survey vessel - Maharaj, U.; Singh, K.; Pike, T.; Pike, C. (International Water Management Institute, 2024)
As part of the CGIAR Initiative on Digital Innovation, GroundTruth, in partnership with the International Water Management Institute (IWMI), investigated the use of Unmanned Aerial Vehicles (UAVs) to aid in performing bathymetric and water quality surveys. A key outcome of the research and development within this collaboration has been the design and construction of a low-cost survey system comprising a survey vessel equipped with multiple sensors that collect water quality and bathymetric data and can be connected to a UAV. Traditional point-sampling methods limit comprehensive assessments of river health over large spatial areas. This challenge was addressed by developing a drone-towed survey vessel for spatially extensive water quality and depth data collection. The aim of developing the survey vessel was to improve the data collection process which could be useful to further develop the linkages between river flow regimes and water quality parameters.